High-dispersion, low-loading and high-activity catalyst as well as preparation method and application thereof

By using the flow-pulse electrodeposition method driven by differential pressure in conductive porous support materials, high dispersion, low loading and high activity catalysts are prepared, which solves the problems of high catalyst preparation cost and complex process in the prior art, and realizes the Low cost and high catalytic activity effects.

CN119386893APending Publication Date: 2025-02-07BEIHANG UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411322783.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing catalyst preparation process has problems such as high cost and complex process routes, making it difficult to achieve low cost and high catalytic activity.

Method used

By using the flow-pulse electrodeposition method driven by pressure differential, a solution containing the metal to be deposited is flowed through the pores of the conductive porous support material and pulsed electrodeposition is performed to prepare a high dispersion, low loading and high activity catalyst.

Benefits of technology

Through this method, the problem of easy agglomeration of conventional electrodeposition catalysts is overcome, the dispersion and catalytic performance of metals are improved, and the breakthrough of low-cost and high catalytic activity is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005056926540000101
    Figure BDA0005056926540000101
  • Figure BDA0005056926540000111
    Figure BDA0005056926540000111
  • Figure BDA0005056926540000141
    Figure BDA0005056926540000141
Patent Text Reader

Abstract

The invention belongs to the technical field of catalyst preparation, and particularly relates to a high-dispersion, low-load and high-activity catalyst as well as a preparation method and application thereof. The preparation method of the high-dispersion, low-loading and high-activity catalyst comprises the following steps: under the driving of pressure difference, enabling a solution containing metal to be deposited to flow through the interior of a pore channel of a conductive porous carrier material, and carrying out pulse electrodeposition, so as to obtain the catalyst with the metal loaded on the conductive porous carrier material. By regulating and controlling the pulse electrodeposition mechanism, the structure, morphology and the like of deposited metal particles can be controlled, the metal can be uniformly distributed in nanopores and on the surface of the conductive porous carrier material, the defect that a conventional electrodeposition catalyst is prone to agglomeration is overcome, the dispersity of the deposited metal is improved, and then the catalytic performance of the metal is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalyst preparation, and specifically relates to a high-dispersion, low-load and high-activity catalyst and a preparation method and application thereof. Background Art

[0002] Catalysts are widely used in both thermal catalysis and electrocatalysis. They can accelerate the reaction process under low-cost conditions. Commonly used catalysts are precious metals, such as Pt, Pd and Ru-based catalysts. Generally, in order to improve the catalytic effect of the catalyst, it is necessary to appropriately increase the precious metal loading, but the cost increases. Therefore, the high cost of catalysts is one of the obstacles to the development of catalysts. The main method to reduce the cost of catalysts is to increase the dispersion and catalytic activity of the catalyst. The preparation method of the catalyst affects the dispersion of the catalyst, and then affects the activity of the catalyst. Commonly used catalyst preparation methods include impregnation-reduction method, solvent-gel method and electrodeposition method.

[0003] In order to further improve the catalytic activity of catalysts, single-atom catalysts have been developed. Single-atom catalysts (SACs) combine the advantages of heterogeneous and homogeneous catalysts and have become a rising star in the field of catalysis. Compared with heterogeneous catalysts, SACs maximize the utilization of atoms, have uniform active sites, high catalytic activity and selectivity; compared with homogeneous catalysts, they have better stability. Confinement effects or chemical synthesis are often used to synthesize metals on carriers, and catalysts can also be prepared by using defects or voids on the carrier. However, these preparation methods are relatively complex, the process is difficult to control, and the reproducibility is poor. Summary of the invention

[0004] Technical problem solved by the present invention: In the prior art, the preparation process of the catalyst has the problems of high cost and complicated process route.

[0005] In response to the above technical problems, the present invention provides a highly dispersed, low-loaded and highly active catalyst and a preparation method and application thereof, achieving a breakthrough in low catalyst cost and high catalytic activity.

[0006] Specifically, the present invention provides the following technical solutions:

[0007] In a first aspect, the present invention provides a method for preparing a catalyst, comprising the following steps:

[0008] Driven by pressure difference, a solution containing the metal to be deposited flows through the pores of the conductive porous carrier material to perform pulse electrodeposition to obtain a catalyst in which the metal is loaded on the conductive porous carrier material.

[0009] Preferably, the conductive porous carrier material includes one or more of metal film, carbon film, carbide film, polymer film, composite film, carbon aerogel, nickel foam, carbon cloth and materials obtained by surface modification of the above materials; wherein the composite film is selected from metal / metal oxide composite film or metal / metal composite film.

[0010] Preferably, the conductive porous carrier material is selected from tubular carbon membrane, tubular niobium carbide membrane, hollow fiber copper membrane or carbon cloth.

[0011] More preferably, the conductive porous support material is selected from tubular carbon membrane, carbon cloth or tubular niobium carbide membrane.

[0012] Preferably, the average pore size of the conductive porous support material is 1 nm to 2 μm.

[0013] Preferably, the average pore size of the conductive porous carrier material is 1 nm to 1 μm.

[0014] Preferably, the average pore size of the conductive porous support material is 1 to 200 nm.

[0015] Preferably, the average pore size of the conductive porous support material is 1 to 50 nm.

[0016] Preferably, the average pore size of the conductive porous support material is 1 to 20 nm.

[0017] Preferably, the average pore size of the conductive porous support material is 1 to 15 nm.

[0018] Preferably, the average pore size of the conductive porous support material is 1 to 10 nm.

[0019] Preferably, the solution containing the metal to be deposited contains one or more metal salts.

[0020] Preferably, the solution contains a metal salt with a concentration of 0.1 to 10 mol / L calculated as metal atoms.

[0021] Preferably, the solution contains salts of two or more metals, and the concentration of each metal atom is 0.05 to 5 mol / L, calculated as metal atoms.

[0022] Preferably, the surface area of ​​the conductive porous support material is 1-100 cm 2 .

[0023] More preferably, the surface area of ​​the conductive porous support material is 10 to 40 cm 2 .

[0024] More preferably, the surface area of ​​the conductive porous carrier material is 20 to 30 cm 2 .

[0025] Preferably, the metal is a catalytically active metal.

[0026] Preferably, the metal is selected from one or more of Pt, Pd, Rh, Ru, Ir, Au, Ag, Cu, Fe, Ni, Co, Cr, Zn and Ba.

[0027] More preferably, the metal is selected from one or more of Pt, Pd, Ru, Ir, Au, Ag and Cu.

[0028] Preferably, the metal is a combination of Cu and Pd.

[0029] Preferably, the mass ratio of Cu to Pd is 1-3:1-3.

[0030] Preferably, the metal is a combination of Pt and Ir.

[0031] Preferably, the mass ratio of Pt to Ir is 1-3:1-3.

[0032] Preferably, the solvent used in the solution containing the metal to be deposited is water.

[0033] Preferably, the temperature of the solution is 25-32°C.

[0034] Preferably, the pressure difference drive is to control the pressure difference by using a metering pump.

[0035] Preferably, the solution containing the metal to be deposited flows into the pores on one side of the conductive porous support material and flows out from the pores on the other side.

[0036] Preferably, the solution containing the metal to be deposited is flowed from top to bottom through the electrically conductive porous support material.

[0037] Preferably, one end of the metal film, carbon film, carbide film, polymer film, composite film, carbon aerogel, nickel foam or a material obtained by surface modification of the above materials is sealed with glue.

[0038] Preferably, the carbon cloth is sealed around with glue.

[0039] Preferably, the solution containing the metal to be deposited flows into the pores on one side of the conductive porous support material and flows out from the pores on the other side.

[0040] Preferably, the solution containing the metal to be deposited flows into the pores on one side of a metal film, a carbon film, a carbide film, a polymer film, a composite film, a carbon aerogel, a nickel foam, or a material obtained by surface modification of the above materials, and flows out from the pores on the other side.

[0041] Preferably, the solution containing the metal to be deposited flows into the pores on one side of the carbon cloth and flows out from the pores on the other side.

[0042] Preferably, the transmembrane pressure difference is 50-100 kPa.

[0043] More preferably, the transmembrane pressure difference is 50 to 70 kPa.

[0044] Preferably, the pulse electrodeposition is performed under the following conditions: the working voltage of the external power source is -1.2 to -0.2 V vs SCE.

[0045] Preferably, the pulse current density is 10 to 100 mA·cm -2 .

[0046] Preferably, the single pulse power-on time in each pulse unit is 0.01 to 1 s.

[0047] Preferably, the single pulse power-on time in each pulse unit is 0.1 to 0.7 s.

[0048] More preferably, the single pulse power-on time in each pulse unit is 0.2 to 0.6 s.

[0049] More preferably, the single pulse power-on time in each pulse unit is 0.3-0.5 s.

[0050] Preferably, the single power-off time in each pulse unit is 0.005 to 20 seconds.

[0051] Preferably, the single power-off time in each pulse unit is 0.005 to 10 seconds.

[0052] More preferably, the single power-off time in each pulse unit is 0.005 to 1 s.

[0053] More preferably, the single power-off time in each pulse unit is 0.005-0.5 s.

[0054] More preferably, the single power-off time in each pulse unit is 0.005-0.3s.

[0055] More preferably, the single power-off time in each pulse unit is 0.005-0.1s.

[0056] More preferably, the single power-off time in each pulse unit is 0.01-0.1s.

[0057] Preferably, the number of pulses of each pulse unit is 40 to 200 times.

[0058] Preferably, the number of pulses of each pulse unit is 40 to 150 times.

[0059] More preferably, the number of pulses of each pulse unit is 40 to 100 times.

[0060] More preferably, the number of pulses of each pulse unit is 70 to 100 times.

[0061] Preferably, the interval time between two pulse units is 0.1-500s.

[0062] Preferably, the interval time between two pulse units is 100-500s.

[0063] More preferably, the interval time between two pulse units is 150-500 s.

[0064] More preferably, the interval time between two pulse units is 250-500 s.

[0065] More preferably, the interval time between two pulse units is 300-500s.

[0066] More preferably, the interval time between two pulse units is 400-500s.

[0067] More preferably, the interval time between two pulse units is 450-500s.

[0068] Preferably, the total deposition time is 0.8 to 800 s.

[0069] Preferably, the total deposition time is 0.8 to 500 s.

[0070] More preferably, the total deposition time is 0.8 to 200 s.

[0071] More preferably, the total deposition time is 50 to 150 seconds.

[0072] More preferably, the total deposition time is 100 to 150 seconds.

[0073] More preferably, the total deposition time is 120 to 150 seconds.

[0074] More preferably, the total deposition time is 130 to 140 seconds.

[0075] In a second aspect, the present invention provides a catalyst prepared by the above preparation method.

[0076] Preferably, the particle size of the metal deposited in the catalyst is the diameter of a metal atom.

[0077] Preferably, the percentage of the metal deposited in the catalyst to the total mass of the conductive porous carrier material is greater than 0 and less than or equal to 0.1%.

[0078] Preferably, the percentage of the metal deposited in the catalyst to the total mass of the conductive porous carrier material is greater than 0 and less than or equal to 0.05%.

[0079] More preferably, the percentage of the metal deposited in the catalyst to the total mass of the conductive porous carrier material is greater than 0 and less than or equal to 0.02%.

[0080] More preferably, the percentage of the metal deposited in the catalyst to the total mass of the conductive porous carrier material is greater than 0 and less than or equal to 0.015%.

[0081] In a third aspect, the present invention provides an application of a catalyst in the field of electrocatalytic degradation of pollutants or electrocatalytic reduction of carbon dioxide.

[0082] Preferably, the catalyst is used in the field of electrocatalytic reduction treatment of nitrate nitrogen.

[0083] Preferably, the catalyst is used in the field of electrocatalytic oxidation treatment of benzyl alcohol.

[0084] Preferably, the catalyst is used in the field of electrocatalytic oxidation treatment of phenol.

[0085] Beneficial Effects of the Invention

[0086] The present invention couples in situ the flow process of a solution containing a metal to be deposited in the pores of a conductive porous carrier material and a pulse electric field process. The flow process can achieve uniform distribution of the metal in the narrow pores and on the surface of the conductive porous carrier material. The pulse electric field mechanism can achieve control of the metal particle structure and morphology. The complementary advantages of the flow process and the pulse electric field process overcome the disadvantage of easy agglomeration of conventional electrodeposition catalysts, improve the dispersion of the metal, and further improve its catalytic performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0087] Figure 1 Schematic diagram of the deposition mechanism of the catalyst preparation of the present invention. 1 is the power-on time of a single pulse of each pulse unit; 2 is the power-off time of a single pulse; 3 is the interval time between two pulse units; 4 is the number of pulses of each pulse unit; and 5 is the total deposition time. Figure 1 It is just for demonstration. The power-on time, power-off time, number of pulses, interval time between two pulse units and total deposition time of each pulse unit shall be subject to actual conditions. The total deposition time is the total deposition time, that is, the total power-on time, excluding the single power-off time of each pulse and the interval time between two pulse units.

[0088] Figure 2The figure is a device diagram for preparing the catalyst of the embodiment of the present invention. Among them, 6-electrochemical workstation; 7-membrane electrode (membrane electrode is the conductive porous carrier material of the present invention); 8-sedimentation tank; 9-counter electrode; 10-reference electrode (reference electrode is saturated calomel electrode (in neutral electrolyte); is mercuric oxide electrode (alkaline electrolyte); is mercuric sulfate electrode (acidic electrolyte)); 11-pressure sensor; 12-metering pump; 13-solution tank.

[0089] Figure 3 This is a diagram of a catalyst preparation device according to an embodiment of the present invention, wherein 14 is a power source (two-electrode system, recording the cell voltage); 15 is a carbon cloth wrapping activated carbon; 16 is an activated carbon cavity; 17 is a sedimentation tank; 18 is a pressure sensor; 19 is a metering pump; and 20 is a solution tank.

[0090] Figure 4 The figure is a diagram of a catalyst preparation device according to an embodiment of the present invention, wherein 21 is an electrochemical workstation; 22 is a membrane electrode; 23 is a deposition tank; 24 is a reference electrode; 25 is a counter electrode; and 26 is a magnetic stirrer.

[0091] Figure 5 The diagrams are the mechanism diagrams of the electrocatalytic oxidation or electrocatalytic reduction of pollutants. (a) is the mechanism diagram of the catalyst prepared by the flow-pulse electrodeposition method for the electrocatalytic reduction of pollutants, and (b) is the mechanism diagram of the catalyst prepared by the flow-pulse electrodeposition method for the electrocatalytic oxidation of pollutants.

[0092] Figure 6 The material characterization diagram of the catalyst (CuPd / CM) in Example 1 in which Cu and Pd diatoms are loaded on a carbon membrane. (a) Surface electron micrograph of CuPd / CM, (b) Cross-section electron micrograph of CuPd / CM, (c) High magnification cross-section electron micrograph of CuPd / CM, (d) EDS result of the cross section of CuPd / CM under a scanning electron microscope, (e) TEM image of CuPd / CM, (f) EDS result of CuPd / CM under a transmission electron microscope, (g) Spherical aberration HAADF-STEM image of CuPd / CM, (h) Spherical aberration HAADF-STEM image of CuPd / CM at a high magnification, (i) Statistical distribution of the distance between Cu / Pd diatomic pairs.

[0093] Figure 7 The atomic structure and chemical state analysis diagrams of the catalyst of Cu and Pd diatomic loading on carbon membrane (CuPd / CM) obtained in Example 1, the catalyst of Cu single atom loading on carbon membrane (Cu / CM) obtained in Example 6, and the catalyst of Pd single atom loading on carbon membrane (Pd / CM) obtained in Example 7.

[0094] Among them, (a) is the C1s XPS spectra of CuPd / CM sample, CuCu / CM sample and PdPd / CM sample. (b) is the Cu K-edge EXAFS spectra in CuPd / CM, CuCu / CM, Cu foil, CuO and Cu2O. (c) PdK-edge EXAFS spectra of CuPd / CM, PdPd / CM, Pd foil and PdO. (d) Fourier transform of Cu k-edge of CuPd / CM, CuCu / CM and Cu foil. (e) Fourier transform of Pd k-edge of CuPd / CM, PdPd / CM and Pd foil. (f) Shell fitting result of EXAFS spectrum of CuPd / CM in R space of Cu k-edge, and the inset is the catalyst loading model. (g) Shell fitting result of EXAFS spectrum of CuPd / CM in R space of Pd K-edge, and the inset is the catalyst loading model: CuPd / CM. (h) Wavelet transform image of Cu from (b) CuPd / CM, (i) Wavelet transform image of Pd K-edge from (c) CuPd / CM. DETAILED DESCRIPTION

[0095] As mentioned above, the object of the present invention is to provide a highly dispersed, low-loaded and highly active catalyst and a preparation method and application thereof.

[0096] Terminology: Transmembrane pressure is the pressure required to drive water through the membrane, which is the difference between the inlet and outlet pressures of the membrane electrode.

[0097] In a first aspect, the present invention provides a method for preparing a highly dispersed, low-loaded and highly active catalyst, comprising the following steps:

[0098] (1) preparing a solution containing a metal salt to be deposited;

[0099] (2) Driven by a pressure difference, a solution containing the metal salt to be deposited flows through the pores of a conductive porous carrier material, an electric field is applied during the flow, pulse electrodeposition is performed, and the pulse electrodeposition mechanism is regulated to obtain a catalyst in which the metal is loaded on the surface and pores of the conductive porous carrier.

[0100] Preferably, the conductive porous carrier material includes one or more of metal film, carbon film, carbide film, polymer film, composite film, carbon aerogel, nickel foam and materials obtained by surface modification of the above materials; wherein the composite film is selected from metal / metal oxide composite film or metal / metal composite film.

[0101] Preferably, the metal film is a porous metal film commonly used in the art.

[0102] More preferably, the metal film is selected from a copper film, an iron film, a palladium film or a nickel film.

[0103] Alternatively, preferably, the carbide film is a porous carbide film commonly used in the art.

[0104] More preferably, the carbide film is selected from a niobium carbide film or a silicon carbide film.

[0105] Alternatively, preferably, the polymer membrane is a porous polymer membrane commonly used in the art.

[0106] More preferably, the polymer membrane is a perfluorosulfonic acid ionomer membrane.

[0107] Alternatively, preferably, the metal / metal oxide composite membrane and the porous metal / metal composite membrane; wherein the metal is selected from one or more of copper, iron and nickel; and / or the metal oxide is selected from one or more of manganese oxide, molybdenum oxide, ruthenium oxide and iridium oxide.

[0108] Alternatively, preferably, in the material obtained by surface-modifying the above-mentioned material, the surface modification is to change the hydrophilicity, hydrophobicity or charge property of the surface of the conductive porous carrier material.

[0109] Preferably, the conductive porous support material is selected from tubular carbon membrane, carbon cloth or tubular niobium carbide membrane.

[0110] More preferably, the conductive porous support material is selected from tubular carbon membranes.

[0111] In the present invention, in the electrocatalytic reduction experiment, the catalyst obtained by using carbon film or carbon cloth as the conductive porous carrier material has a more excellent effect; in the electrocatalytic oxidation experiment, the catalyst obtained by using niobium carbide film as the conductive porous carrier material has a more excellent effect.

[0112] Preferably, the average pore size of the conductive porous carrier material is 1 nm to 2 μm. If the pore size is too small, the pressure difference is large and the energy consumption is increased; if the pore size is too large, a highly dispersed catalyst cannot be obtained.

[0113] Preferably, the metal salt includes one or more of Cu(NO3)2, Pd(NO3)2, HAuCl4, IrCl3, RuCl3, H2PtCl6 and AgNO3.

[0114] Preferably, the concentration of each metal salt is 0.05 to 5 mmol / L. Too high a concentration of the metal salt will cause the deposited metal atoms to agglomerate, and too low a catalyst concentration will reduce the catalytic sites, resulting in a decrease in catalytic performance.

[0115] The present invention has no special limitation on the external power supply, as long as it can provide a stable voltage. Preferably, the working potential of the external power supply is -1.2 to -0.2 V vs SCE.

[0116] Preferably, the pulse current density is 10 to 100 mA·cm -2 .

[0117] Preferably, the single pulse power-on time in each pulse unit is 0.01 to 1 s; the single power-off time in each pulse unit is 0.005 to 20 s; the number of pulses in each pulse unit is 40 to 200 times; the interval time between two pulse units is 0.1 to 500 s; and the total deposition time is 0.8 to 800 s.

[0118] Preferably, the effect of the catalyst obtained by pulse electrodeposition is better than that of the catalyst obtained by non-pulse electrodeposition.

[0119] In the present invention, the counter electrode is a conventional conductive material. Preferably, the counter electrode is stainless steel, a graphite plate or a carbon electrode; the counter electrode is arranged near the working electrode (conductive porous carrier material). The conductive porous carrier material, the external power supply, the counter electrode and the metal salt solution constitute a current loop.

[0120] In the present invention, the strong interaction between the metal and the conductive porous carrier material can make the catalyst more stable and have stronger catalytic activity.

[0121] In the present invention, the pressure differential drive refers to the metering pump extracting the solution in the solution tank and sending it to the membrane tube in the conductive porous carrier material. Due to the small pore size of the membrane tube, the solution transported by the metering pump will cause a certain positive pressure under the condition of a certain flow rate, prompting the solution to enter the membrane pores, thereby achieving pressure drive. The flow direction of the deposition liquid is the pressure differential drive direction.

[0122] Figure 1 This is a schematic diagram of the deposition mechanism of the catalyst preparation of the present invention. As shown in the figure, the present invention uses a conductive porous carrier material as a cathode, applies a positive pressure, and allows a solution containing a metal to be deposited to pass through the membrane pores of the conductive porous carrier material. A pulsed electric field is applied during the flow of the solution to allow the metal to be uniformly deposited inside and on the surface of the membrane pores.

[0123] The present invention has no special limitation on the reaction device used in the method for preparing the highly dispersed, low-loaded and highly active catalyst, as long as it can realize the technical scheme of the above-mentioned preparation method. Preferably, in the embodiment of the present invention, the structure of the reaction device used is as shown in Figure 2-4 The specific structures are described in the relevant embodiments, but these reactor structures are not limitations on the preparation methods of the embodiments, and the solutions of the embodiments of the present invention can still be implemented by selecting reactors with other structures.

[0124] In the present invention, Figure 2 and Figure 3The deposition process of pulse electrodeposition includes the following steps: the deposition tank and the solution tank are filled with a solution containing the metal to be deposited. The solution to be deposited in the solution tank is driven by a metering pump to flow from the solution tank to the deposition tank, passing through the membrane pores of the conductive porous carrier material. In the process of flowing through the membrane pores, the metal catalyst is uniformly deposited in the membrane pores and on the surface of the conductive porous carrier material under the action of the electric field.

[0125] In the present invention, Figure 4 The deposition process of pulse electrodeposition includes the following steps: the deposition tank is filled with the metal salt solution and electrolyte solution to be deposited. The magnetic stirrer is turned on to enhance mass transfer, ensure that the metal salt is not enriched on the membrane surface, and eliminate concentration polarization.

[0126] In the present invention, Figure 5 (a) is a mechanism diagram of the electrocatalytic reduction of pollutants by a catalyst prepared by flow-pulse electrodeposition, and (b) is a mechanism diagram of the electrocatalytic oxidation of pollutants by a catalyst prepared by flow-pulse electrodeposition. Figure 5 In the embodiment, the transverse channel is the membrane pore channel, and the longitudinal channel is the hollow tube of the membrane tube. The membrane pore channel is the main part for depositing metal, and the hollow tube part is the channel through which the solution of the metal to be deposited passes. The metal salt solution flows from top to bottom. Since the tail of the hollow tube of the membrane tube is sealed by epoxy glue, the solution of the metal to be deposited can only flow out through the membrane pore channel. The longer the hollow tube part is, the more membrane pore channels the solution of the metal to be deposited can flow through. When the solution of the metal to be deposited flows through the conductive porous carrier material, the metal is uniformly deposited in the pore channels of the conductive porous carrier material by applying an electric field. The dispersion and morphology of the metal in the pore channel can be controlled by adjusting the pulse electric field mechanism. In the present invention, by applying an electric field, the metal salt ions in the solution of the metal to be deposited undergo an electron gain and loss process, and are loaded on the conductive porous carrier material in the form of metal atoms. In the present invention, the electric field is applied in the form of continuous multiple pulses, and the deposition potential, the single power-on time of each pulse unit, the single power-on interval or the single power-on unit time and other conditions are adjusted to control the deposited metal to obtain a catalyst with uniformly dispersed metal atoms.

[0127] The present invention has no particular limitation on the source of the pressure difference. Any device that can provide positive pressure and is well known to those skilled in the art can be selected. In the embodiment of the present invention, the pressure difference drive is specifically provided by a metering pump. The transmembrane pressure difference is the pressure difference between the feed side and the discharge side of the membrane. Preferably, the transmembrane pressure difference is 50-100 kPa.

[0128] The present invention has no particular limitation on the connection method of connecting the conductive porous carrier material and the counter electrode to the external power source, and any connection method well known to those skilled in the art can be used.

[0129] After the conductive porous carrier material and the counter electrode are connected to an external power source, the solution containing the metal to be deposited flows through the membrane pores of the conductive porous carrier material under the pressure difference driving, and the electrodeposition is performed to obtain a catalyst supported on the conductive porous carrier material. The present invention has no particular limitation on the source of the pressure difference, and a device that can provide positive pressure known to those skilled in the art can be selected. Preferably, in an embodiment of the present invention, the pressure difference driving is specifically provided by a metering pump.

[0130] The present invention does not have any special restrictions on the conditions for preparing the highly dispersed, low-loaded and highly active catalyst (such as transmembrane pressure difference, water temperature, etc.), and specific adjustments can be made according to the structure of the reactor used.

[0131] In the present invention, the preparation steps of the membrane electrode include: sealing one end of the conductive porous carrier material with epoxy glue, so that the conductive porous membrane tube on one side is sealed, so that the solution flows in from the hollow tube of the membrane tube and flows out from the membrane pores. The sealed conductive porous carrier is used as a membrane electrode.

[0132] In the present invention, the electrode area refers to the surface area of ​​the porous conductive carrier.

[0133] Unless otherwise specified, various reagents / instruments used in the examples and comparative examples of the present invention are conventional commercially available products.

[0134] Table 1 Manufacturers of experimental reagents / instruments

[0135]

[0136]

[0137] Among them, the preparation method of a tubular carbon membrane with an average pore size of 8.3nm includes the following steps (the preparation method refers to patent CN102107123A): Resorcinol (R) and formaldehyde (F) are prepared into a water solution with a total concentration of 20% (the mass sum of resorcinol and formaldehyde divided by the total volume of the solution) according to the ratio of R:F (molar ratio) = 1:2, and the aqueous solution contains hexadecyltrimethylammonium bromide, and the content is 1 / 500 of the molar number of resorcinol. The prepared solution is sealed in a ground-mouth bottle and placed in an oven for reaction for 19 hours to obtain a sol. The sol is taken out and cooled to room temperature. A homemade tubular ceramic membrane with an average pore size of 0.35 microns was used as the support, and the sol was coated on the surface of the support by an immersion pulling method. The coated support was placed in an environment saturated with formaldehyde vapor for gelation and drying for 48 hours, then dried at room temperature for 48 hours, and then placed in a tubular carbonization furnace for carbonization. The final carbonization temperature was 800°C, and the final temperature residence time was 2 hours. After the carbonization was completed, it was naturally cooled to room temperature with the furnace, i.e., an 8.3nm tubular carbon membrane.

[0138] The preparation method of the tubular niobium carbide membrane with an average pore size of 8.3 nm comprises the following steps: mixing niobium pentoxide nanopowder with methylcellulose and water in proportion, wherein the percentages of methylcellulose, niobium pentoxide, water and glycerol are 1.71w%, 74.36w%, 17.06w% and 6.87w% respectively, and using a membrane extruder to obtain a niobium pentoxide tubular membrane. Drying for 1-2 days at room temperature, after surface treatment, placing in a muffle furnace, heating to 1100°C at a heating rate of 3°C / min, and cooling naturally to obtain a niobium pentoxide tubular membrane, placing the niobium pentoxide membrane in a high-temperature tubular furnace, heating to a final temperature of 1050°C at a heating rate of 2°C / min, and keeping the temperature for 8 hours (the volume ratio of atmosphere: methane and argon is 1:9:), and cooling naturally to obtain a dark brown niobium carbide membrane.

[0139] The highly dispersed, low-loaded and highly active catalyst of the present invention and its preparation method and application are further illustrated by specific examples below.

[0140] Example 1

[0141] This embodiment adopts Figure 2 The device shown in the figure, the method for preparing the catalyst comprises the following steps:

[0142] The sedimentation tank 8 is filled with 150 mL of a mixed solution having a temperature of 25 to 32° C. The mixed solution includes 0.5 mol·L -1 NH4Cl, 0.5mmol·L -1 Cu(NO3)2 and 0.5mmol·L -1 The solution tank 13 is filled with the same solution as that in the deposition tank 8. The electrochemical workstation 6 is turned on, and voltage is applied to the membrane electrode 7 and the counter electrode 9. The solution in the solution tank 13 flows from top to bottom through the conductive porous membrane (i.e., the conductive porous carrier material) in the membrane electrode 7 driven by the pressure difference of the metering pump 12, and flow-pulse electrodeposition is performed. The deposited solution enters the deposition tank 8; wherein the metal ions in the solution are uniformly deposited on the surface and pores of the conductive porous membrane to complete the deposition.

[0143] The conductive porous membrane is a tubular carbon membrane with an average pore size of 8.3 nm (electrode area of ​​28 cm 2 ), one end of the tubular carbon membrane is sealed with epoxy glue, which is the cathode, the platinum sheet is the anode (counter electrode), and the saturated calomel electrode is the reference electrode 10, so that the metal salt solution in the solution tank 13 flows from the hollow tube of the membrane tube in the tubular carbon membrane from top to bottom through the pressure difference, and flows out from the membrane pores, and at the same time, a pulse electric field is applied on the surface of the cathode electrode. Set the processing conditions: transmembrane pressure difference 50kPa, working voltage -0.8Vvs.SCE, pulse current density: 10~100mA / cm 2In each pulse unit: the power-on time of a single pulse is 0.4s, the power-off time is 0.05s, and the number of pulses is 84 times; the interval between two pulse units is 484s, and the total deposition time is 134.4s (the total deposition time refers to the total power-on time, excluding the power-off time and the interval time). After the reaction is completed, the tubular carbon membrane with deposited metal is taken out, rinsed with deionized water several times, and then soaked in deionized water, changing the water every 6 hours for 48 hours, and dried at room temperature for use.

[0144] The preparation method is used to obtain a tubular carbon membrane catalyst loaded with Cu and Pd, wherein the percentage of Cu in the total mass of the tubular carbon membrane is 0.005%, and the percentage of Pd in ​​the total mass of the tubular carbon membrane is 0.005%.

[0145] from Figure 6 As can be seen from the ac in the surface electron microscopy image and the cross-sectional electron microscopy image, there are no obvious nanoparticles; Figure 6 As can be seen from the d in the figure, EDS shows obvious Cu and Pd elements; Figure 6 As can be seen from e in the figure, there are no obvious nanoparticles in the TEM image; Figure 6 As can be seen from f in the figure, EDS shows obvious Cu and Pd elements; Figure 6 As can be seen from the gh in the spherical aberration electron microscope image, Cu and Pd are in diatomic form; Figure 6 It can be seen from the i in that the distance between two adjacent atoms is mainly 0.25nm.

[0146] from Figure 7 It can be seen from a in that in the XPS spectra of C1s of the CuPd / CM sample (obtained in Example 1), the CuCu / CM sample (obtained in Example 6) and the PdPd / CM sample (obtained in Example 7), the peak at 285 eV is the CC bond, the peak at 289.5 eV in the CuPd / CM sample is the C=O bond, and the C=O peak in the CuCu / CM and PdPd / CM samples shifts to the negative direction. This is due to the presence of Cu-Cu bonds and Pd-Pd bonds, indicating that Cu and Pd in ​​the CuPd / CM sample form diatomic Cu-Pd on the carbon substrate.

[0147] In the X-ray absorption near-edge structure spectrum of elemental Cu ( Figure 7 In b), the element Cu in the CuPd / CM sample exists in an oxidation state between Cu2O(1+) and CuO(2+). Figure 7As can be seen from c in the figure, the X-ray absorption near-edge structure spectrum of element Pd in ​​the CuPd / CM sample is between that of Pd foil and PdO, and element Pd also exists in an oxidized state. Compared with the X-ray absorption near-edge structure spectrum of element Cu in the CuCu / CM sample, the X-ray absorption near-edge structure spectrum of element Cu in the CuPd / CM sample moves toward a higher energy direction, indicating that the introduction of metal Pd increases the oxidation state of element Cu; compared with the sample PdPd / CM, the charge transfer from atomic Pd to atomic Cu in the sample CuPd / CM reduces the Cu atoms. The K3-weighted Fourier transform ( Figure 7 d), the main peaks of samples CuPd / CM, CuCu / CM and PdPd / CM are located at The second peaks of samples CuCu / CM and CuPd / CM are located at 2.36 and 2.76, respectively. Corresponding to the first shell Cu foil (atomic distance This indicates the presence of metal-metal diatomic coordination. Similarly, the second peak of samples PdPd / CM and CuPd / CM is located at 2.37 and Corresponding to the first shell Pd foil (atomic distance ( Figure 7 e), further proving the existence of metal-metal diatomic coordination. The Fourier transform of the X-ray absorption near-edge structure spectrum was fitted ( Figure 7 f and g), the fitting peak positions are located at 1.57 and They correspond to the Cu-C and Pd-C coordination shells, respectively, and the coordination numbers of Cu-C and Pd-C are 4. The second peak of the fitting is located at The fitting data show that Cu-Pd forms a diatomic structure. The wavelet transform of EXAFS spectrum shows that CuCu / CM and CuPd / CM are at about 4.12 and The intensity maximum is shown at about 4.46 and 1.37, which corresponds to the Cu-C path in the Cu K near-edge spectrum. The maximum intensity is shown at , which corresponds to the Pd-C path in the PdK near-edge spectrum. For the CuPd / CM sample, the maximum intensity of the wavelet transform of the Cu and Pd near-edge signals is located at The strength of the metal-metal bond is between that of CuCu / CM and PdPd / CM. The wavelet transform results further confirmed that the sample CuPd / CM has metal-carbon coordination and metal-metal diatomic coordination ( Figure 7 h and i in ).

[0148] Electrocatalytic reduction of nitrate nitrogen experiment

[0149] A three-electrode system was used to prepare a tubular carbon membrane loaded with Cu and Pd as a membrane electrode (electrode area of ​​28 cm 2 ), saturated calomel as reference electrode, platinum sheet as counter electrode. Prepare 0.05mol / L sodium nitrate solution, add 0.5mol / L sodium sulfate as supporting electrolyte, pH of the solution is 6.5, apply voltage of -4V vs SCE, and conduct nitrate nitrogen reduction experiment. Its mechanism is as follows Figure 5 As shown in a, the pollutants containing nitrate flow into the hollow tube of the membrane tube, pass through the membrane pores deposited with metal, and flow out from the membrane pores. The transmembrane pressure difference is 50kPa. The reactor used in this experiment is continuous. After power is turned on, the mixed solution containing nitrate (0.05mol / L sodium nitrate and 0.5mol / L sodium sulfate) will continuously flow into the hollow tube of the membrane tube and flow out from the membrane pores. The reaction time is 10h, and samples are taken every half an hour to calculate the one-way removal rate of nitrate nitrogen in the solution and the selectivity of nitrogen.

[0150] The calculation formula for the one-way removal rate of nitrate nitrogen is as follows:

[0151]

[0152] Wherein, τ represents the one-way removal rate of nitrate nitrogen (%); c0 represents the concentration of nitrate in the mixed solution at the initial time; c t Expressed as the concentration of nitrate in the mixed solution at the end time.

[0153] The calculation formula of nitrogen selectivity is as follows:

[0154]

[0155] Among them, S i It is expressed as nitrogen selectivity (%); C0 is the concentration of nitrate in the mixed solution at the initial time; C t Expressed as the concentration of nitrate in the mixed solution at the end time; C i Indicates the concentration of nitrogen.

[0156] Conclusion: The tubular carbon membrane catalyst loaded with Cu and Pd was applied to the electrocatalytic reduction of nitrate nitrogen. During the 10-hour reaction, the single-pass removal rate of nitrate nitrogen and the nitrogen selectivity could reach 100% in the samples taken at half-hour intervals.

[0157] Example 2

[0158] This embodiment adopts Figure 2 The device shown in the figure, the method for preparing the catalyst comprises the following steps:

[0159] The sedimentation tank 8 is filled with 150 mL of a mixed solution having a temperature of 25 to 32° C. The mixed solution includes 0.1 mol·L -1 NaCl and 0.5mmol·L -1 HAuCl4. The solution tank 13 is filled with the same solution as that in the deposition tank 8. The electrochemical workstation 6 is turned on, and voltage is applied to the membrane electrode 7 and the housing of the counter electrode 9. The solution in the solution tank 13 flows from top to bottom through the conductive porous membrane driven by the pressure difference of the metering pump 12 to perform flow-pulse electrodeposition. The deposited solution enters the deposition tank 8; wherein the metal ions in the solution are uniformly deposited on the surface and pores of the conductive porous membrane to complete the deposition.

[0160] The conductive porous membrane is a tubular carbon membrane with an average pore size of 8.3 nm (electrode area of ​​28 cm 2 ), one end of the tubular carbon membrane is sealed with epoxy glue, which is the cathode, the platinum sheet is the anode (counter electrode), and the saturated calomel electrode is the reference electrode 10, so that the metal salt solution in the solution tank 13 flows from the hollow tube of the membrane tube in the tubular carbon membrane from top to bottom through the pressure difference, and flows out from the membrane pores, and at the same time, a pulse electric field is applied on the surface of the cathode electrode. Set the processing conditions: transmembrane pressure difference 50kPa, working voltage -0.2Vvs.SCE, pulse current density: 10~100mA / cm 2 In each pulse unit: the power-on time of a single pulse is 0.4s, the power-off time is 0.05s, and the number of pulses is 84; the interval between two pulse units is 484s, and the total deposition time is 134.4s. After the reaction is completed, the tubular carbon membrane with deposited metal is taken out, rinsed with deionized water several times, and then soaked in deionized water, changing the water every 6h for 48h, and dried at room temperature for use.

[0161] The preparation method is used to obtain: a tubular carbon membrane catalyst loaded with Au, wherein the percentage of Au in the total mass of the tubular carbon membrane is 0.01%.

[0162] Experiment on electrocatalytic oxidation of benzyl alcohol

[0163] A three-electrode system was used, and the prepared Au-loaded tubular carbon membrane was used as the membrane electrode (electrode area 28 cm 2 ), which is also the anode of the electrocatalytic oxidation experimental system. The reference electrode is a saturated calomel electrode, and the counter electrode is a platinum electrode. Prepare a 0.1 mol / L benzyl alcohol solution, add 1 mol / L KOH as a supporting electrolyte, the pH of the solution is 6.5, and the applied current density is 20 mA cm -2 , benzyl alcohol oxidation experiment was carried out, the mechanism diagram is shown in Figure 5As shown in Figure b, pollutants flow into the hollow tube of the membrane tube, pass through the membrane pores deposited with metal, and flow out from the membrane pores. The transmembrane pressure difference is 50 kPa. The reactor used in this experiment is continuous. After power is turned on, the mixed solution containing benzyl alcohol (1 mol / L KOH and 0.1 mol / L benzyl alcohol) will continuously flow into the hollow tube of the membrane tube and flow out from the membrane pores. The reaction time is 10 hours, and samples are taken every half an hour to measure and calculate the one-way removal rate of benzyl alcohol in the solution.

[0164] Among them, the calculation formula for the single-pass removal rate of benzyl alcohol is as follows:

[0165] τ= (C0-C t ) ×100%

[0166] C0

[0167] Wherein, τ represents the one-way removal rate of benzyl alcohol (%); C0 represents the concentration of benzyl alcohol in the mixed solution at the initial time; C t It is expressed as the concentration of benzyl alcohol in the mixed solution at the end time.

[0168] Conclusion: The Au-loaded tubular carbon membrane catalyst was used for electrocatalytic oxidation to remove benzyl alcohol from water. During the 10-hour reaction, the single-pass removal rate of benzyl alcohol in the samples taken at half-hour intervals could reach 100%.

[0169] Example 3

[0170] This embodiment adopts Figure 2 The device shown in the figure, the method for preparing the catalyst comprises the following steps:

[0171] The sedimentation tank 8 is filled with a mixed solution, the temperature of the solution is 25-32°C, and the mixed solution includes 1.0 mmol·L -1 IrCl3 and 0.5 mol·L -1 The solution tank 13 is filled with the same solution as that in the deposition tank 8. The electrochemical workstation 6 is turned on, and voltage is applied to the membrane electrode 7 and the housing of the counter electrode 9. The solution in the solution tank 13 flows from top to bottom through the conductive porous membrane driven by the pressure difference of the metering pump 12 to perform flow-pulse electrodeposition. The deposited solution enters the deposition tank 8; the metal ions in the solution are uniformly deposited on the surface and pores of the conductive porous membrane to complete the deposition.

[0172] The conductive porous membrane is a tubular niobium carbide membrane with an average pore size of 8.3 nm (electrode area of ​​28 cm 2), one end of the tubular niobium carbide membrane is sealed with epoxy glue, which is the cathode, the platinum sheet is the anode (counter electrode), and the saturated calomel electrode is the reference electrode 10, so that the metal salt solution in the solution tank 13 flows from the hollow tube of the membrane tube in the tubular niobium carbide membrane from top to bottom through the pressure difference, and flows out from the membrane pores, and at the same time, a pulse electric field is applied on the surface of the cathode electrode. Set the processing conditions: transmembrane pressure difference 50kPa, working voltage -0.5V vs.SCE, pulse current density: 10~100mA / cm 2 In each pulse unit: the power-on time of a single pulse is 0.4s, the power-off time is 0.05s, and the number of pulses is 84; the interval between two pulse units is 484s, and the total deposition time is 134.4s. After the reaction is completed, the tubular niobium carbide film of the deposited metal is taken out, rinsed with deionized water several times, and then soaked in deionized water, changing the water every 6h for 48h, and dried at room temperature for use.

[0173] The preparation method is used to obtain: an Ir-loaded tubular niobium carbide film catalyst, wherein the percentage of Ir in the total mass of the tubular niobium carbide film is 0.01%.

[0174] Experiment on electrocatalytic oxidation of phenol

[0175] The prepared Ir-loaded tubular niobium carbide film was used as the anode (electrode area 28 cm 2 ), and the platinum electrode was used as the cathode. A 100 mg / L phenol solution was prepared, and 0.1 mol / L Na2SO4 was added as the supporting electrolyte. The pH of the solution was 6.5, and a constant current density of 20 mA cm was applied. -2 , phenol oxidation experiment was carried out, and its mechanism is as follows Figure 5 As shown in b, the pollutants flow in from the hollow tube of the membrane tube, pass through the membrane pores with metal deposits, and flow out from the membrane pores. The transmembrane pressure difference is 50kPa. The reactor used in this experiment is continuous. After power is turned on, the mixed solution containing phenol (100mg / L phenol and 0.1mol / L Na2SO4) will continuously flow in from the hollow tube of the membrane tube and flow out from the membrane pores. The reaction time is 10 hours, and samples are taken every half an hour to calculate the one-way removal rate of phenol and COD in the solution.

[0176] Among them, the calculation formula of the one-way removal rate of phenol is as follows:

[0177]

[0178] Wherein, τ represents the one-way removal rate of phenol (%); C0 represents the concentration of phenol in the mixed solution at the initial time; C t It is expressed as the concentration of phenol in the mixed solution at the end time.

[0179]

[0180] The COD value before removal refers to the COD value in the original water body, and the COD value after removal refers to the COD value in the treated water body. The unit of COD is milligrams per liter.

[0181] Conclusion: The Ir-loaded tubular niobium carbide membrane catalyst was used for the electro-oxidation removal of phenol from organic matter. During the 10 hours of reaction, the phenol removal rate and COD (chemical oxygen demand) removal rate both reached 95% in the samples taken at half-hour intervals.

[0182] Example 4

[0183] This embodiment adopts Figure 4 The preparation device of the catalyst comprises the following steps:

[0184] The sedimentation tank 23 is filled with a mixed solution, the temperature of the solution is 25-32°C, and the mixed solution includes: 0.5 mmol·L -1 RuCl3, 0.5mmol·L -1 H2PtCl6 and 0.5mol·L -1 The electrochemical workstation 21 is turned on, voltage is applied to the membrane electrode 22 and the counter electrode 25, and the magnetic stirrer 26 is turned on for stirring to perform pulse electrodeposition.

[0185] The conductive porous membrane is a tubular niobium carbide membrane with an average pore size of 8.3 nm (electrode area of ​​28 cm 2 ), one end of the tubular niobium carbide membrane is sealed with epoxy glue, which is the cathode, the platinum sheet is the anode (counter electrode), and the saturated calomel electrode is the reference electrode. A pulsed electric field is applied to the electrode surface, and the mass transfer is enhanced by magnetic stirring (only a small part of the metal salt solution flows into the pores of the tubular niobium carbide membrane). Set the processing conditions: working voltage -0.5V vs.SCE, pulse current density: 10~100mA / cm 2 In each pulse unit: the power-on time of a single pulse is 0.4s, the power-off time is 0.05s, and the number of pulses is 84; the interval between two pulse units is 484s, and the total deposition time is 134.4s. After the reaction is completed, the tubular niobium carbide film of the deposited metal is taken out, rinsed with deionized water several times, and then soaked in deionized water, changing the water every 6h for 48h, and dried at room temperature for use.

[0186] The preparation method is used to obtain a tubular niobium carbide film catalyst loaded with Ru and Pt, wherein Ru accounts for 0.005% of the total mass of the tubular niobium carbide film, and Pt accounts for 0.005% of the total mass of the tubular niobium carbide film.

[0187] Experiment on electrocatalytic oxidation of phenol

[0188] The prepared tubular niobium carbide film loaded with Ru and Pt was used as the anode to carry out an electrocatalytic oxidation experiment of phenol. The experimental steps were the same as those of the electrocatalytic oxidation of phenol in Example 3.

[0189] Conclusion: The tubular niobium carbide membrane catalyst loaded with Ru and Pt was used for the electro-oxidation removal of phenol from organic matter. During the 10 hours of reaction, the phenol removal rate and COD (chemical oxygen demand) removal rate were 65% and 40% respectively in the samples taken at half an hour intervals.

[0190] Example 5

[0191] This embodiment adopts Figure 3 The catalyst preparation method comprises the following steps:

[0192] The sedimentation tank 17 is filled with 150 mL of a mixed solution, the temperature of which is 25 to 32° C. The mixed solution includes: 0.5 mol·L -1 NH4Cl, 0.5mmol·L -1 Cu(NO3)2 and 0.5mmol·L -1 Pd(NO3)2, the solution in the solution tank 20 and the sedimentation tank 17 is the same.

[0193] The cathode is made of activated carbon cloth (10 g of activated carbon is filled between two pieces of carbon cloth, and the carbon cloth is sealed with epoxy glue). The average pore size of the carbon cloth is 1.2 nm (the electrode area is 28 cm 2 ), stainless steel is the pressure shell and also serves as the anode (counter electrode), and the surroundings and corners are completely pressed by sealing rings. Driven by the pressure difference, the metal salt solution first enters the stainless steel shell on one side from the inlet, then passes through the pores of the carbon cloth into the stainless steel shell on the other side, and finally flows out from the outlet. At the same time, a pulse electric field is applied on the electrode surface. Set the processing conditions: transmembrane pressure difference 50kPa, working voltage -0.8V vs.SCE, pulse current density: 10~100mA / cm 2 In each pulse unit: the power-on time of a single pulse is 0.4s, the power-off time is 0.05s, and the number of pulses is 84; the interval between two pulse units is 484s, and the total deposition time is 134.4s. After the reaction is completed, the carbon cloth with deposited metal is taken out, rinsed with deionized water several times, and then soaked in deionized water, changing the water every 6h for 48h, and dried at room temperature for use.

[0194] The above preparation method obtains: a carbon cloth catalyst loaded with Cu and Pd, wherein the percentage of Cu in the total mass of the carbon cloth is 0.005%, and the percentage of Pd in ​​the total mass of the carbon cloth is 0.005%.

[0195] Electrocatalytic reduction of nitrate nitrogen experiment

[0196] With activated carbon wrapped with Cu and Pd loaded carbon cloth as membrane electrode, stainless steel as pressure shell and also as anode (counter electrode), 0.05mol / L sodium nitrate solution was prepared, 0.5mol / L sodium sulfate was added as supporting electrolyte, the pH of the solution was 6.5, the applied voltage was -4V vs SCE, and the electrocatalytic reduction of nitrate nitrogen experiment was carried out. The mixed solution containing nitrate first enters the stainless steel shell on one side from the entrance, then enters the stainless steel shell on the other side through the pores deposited with metal in the carbon cloth, and finally flows out from the outlet, and the transmembrane pressure difference is 50kPa. The reactor used in this experiment is carried out continuously. After power is turned on, the mixed solution containing nitrate (0.05mol / L sodium nitrate and 0.5mol / L sodium sulfate) will continuously flow into the stainless steel shell on one side, pass through the carbon cloth, and flow out from the stainless steel shell on the other side. The reaction time is 10h, and the sampling is taken at intervals of half an hour to calculate the one-way removal rate of nitrate nitrogen in the solution and the selectivity of nitrogen. The calculation formula of the one-way removal rate of nitrate nitrogen and the selectivity of nitrogen is the same as that in Example 1.

[0197] Conclusion: Carbon cloth loaded with Cu and Pd was used for electrocatalytic reduction of nitrate nitrogen. During the 10-hour reaction, the single-pass removal rate of nitrate nitrogen reached 100% in the samples taken at half-hour intervals, and the nitrogen selectivity could reach 100%.

[0198] Example 6

[0199] This embodiment adopts Figure 2 The device shown in the figure, the method for preparing the catalyst comprises the following steps:

[0200] The sedimentation tank 8 is filled with 150 mL of a mixed solution at a temperature of 25 to 32°C. The mixed solution includes 0.5 mol·L -1 NH4Cl, 1mmol·L -1 The solution tank 13 is filled with the same solution as that in the deposition tank 8. The electrochemical workstation 6 is turned on, and voltage is applied to the membrane electrode 7 and the counter electrode 9. The solution in the solution tank 13 flows from top to bottom through the conductive porous membrane driven by the pressure difference of the metering pump 12 to perform flow-pulse electrodeposition. The deposited solution enters the deposition tank 8; wherein the metal ions in the solution are uniformly deposited on the surface and pores of the conductive porous membrane to complete the deposition.

[0201] The conductive porous membrane is a tubular carbon membrane with an average pore size of 8.3 nm (electrode area of ​​28 cm 2), seal one end of the tubular carbon membrane with epoxy glue, which is the cathode, platinum sheet as the anode (counter electrode), saturated calomel electrode as the reference electrode, so that the metal salt solution in the solution tank is driven by pressure difference from top to bottom from the hollow tube of the membrane tube in the tubular carbon membrane, and flows out from the membrane pores, while applying a pulse electric field on the surface of the cathode electrode. Set the processing conditions: transmembrane pressure difference 50kPa, working voltage -0.8Vvs.SCE, pulse current density: 10~100mA / cm 2 In each pulse unit: the power-on time of a single pulse is 0.4s, the power-off time is 0.05s, and the number of pulses is 84; the interval between two pulse units is 484s, and the total deposition time is 134.4s. After the reaction is completed, the tubular carbon membrane with deposited metal is taken out, rinsed with deionized water several times, and then soaked in deionized water, changing the water every 6h for 48h, and dried at room temperature for use.

[0202] The above preparation method obtains: a tubular carbon membrane catalyst loaded with Cu, wherein the percentage of Cu in the total mass of the tubular carbon membrane is 0.01%.

[0203] Electrocatalytic reduction of nitrate nitrogen experiment

[0204] The electrocatalytic reduction of nitrate nitrogen experiment was carried out using the Cu-loaded tubular carbon membrane as the membrane electrode. The experimental processing steps were the same as the electrocatalytic reduction of nitrate nitrogen experimental steps in Example 1.

[0205] Conclusion: The Cu-loaded carbon film catalyst was used for the electrocatalytic reduction of nitrate nitrogen. During the 10-hour reaction, the single-pass removal rate of nitrate nitrogen reached 60% in the samples taken at half-hour intervals, and the nitrogen selectivity could reach 10%.

[0206] Example 7

[0207] This embodiment adopts Figure 2 The device shown in the figure, the method for preparing the catalyst comprises the following steps:

[0208] The sedimentation tank 8 is filled with 150 mL of a mixed solution at a temperature of 25 to 32°C. The mixed solution includes 0.5 mol·L -1 NH4Cl, 1mmol·L -1 The solution tank 13 is filled with the same solution as that in the deposition tank 8. The electrochemical workstation 6 is turned on, and voltage is applied to the membrane electrode 7 and the counter electrode 9. The solution in the solution tank 13 flows from top to bottom through the conductive porous membrane driven by the pressure difference of the metering pump 12 to perform flow-pulse electrodeposition. The deposited solution enters the deposition tank 8; wherein the metal ions in the solution are uniformly deposited on the surface and pores of the conductive porous membrane to complete the deposition.

[0209] The conductive porous membrane is a tubular carbon membrane with an average pore size of 8.3 nm (electrode area of ​​28 cm 2 ), seal one end of the tubular carbon membrane with epoxy glue, which is the cathode, platinum sheet as the anode (counter electrode), saturated calomel electrode as the reference electrode, so that the metal salt solution in the solution tank is driven by pressure difference from top to bottom from the hollow tube of the membrane tube in the tubular carbon membrane, and flows out from the membrane pores, while applying a pulse electric field on the surface of the cathode electrode. Set the processing conditions: transmembrane pressure difference 50kPa, working voltage -0.8Vvs.SCE, pulse current density: 10~100mA / cm 2 In each pulse unit: the power-on time of a single pulse is 0.4s, the power-off time is 0.05s, and the number of pulses is 84; the interval between two pulse units is 484s, and the total deposition time is 134.4s. After the reaction is completed, the tubular carbon membrane with deposited metal is taken out, rinsed with deionized water several times, and then soaked in deionized water, changing the water every 6h for 48h, and dried at room temperature for use.

[0210] The above preparation method obtains: a Pd-loaded tubular carbon membrane catalyst, wherein the percentage of Pd in ​​the total mass of the tubular carbon membrane is 0.01%.

[0211] Electrocatalytic reduction of nitrate nitrogen experiment

[0212] The electrocatalytic reduction of nitrate nitrogen experiment was carried out using the Pd-loaded tubular carbon membrane as the membrane electrode. The experimental processing steps were the same as the electrocatalytic reduction of nitrate nitrogen experimental steps in Example 1.

[0213] Conclusion: The Pd-loaded carbon membrane catalyst was used for the electrocatalytic reduction of nitrate nitrogen. During the 10-hour reaction, the single-pass removal rate of nitrate nitrogen reached 15% in the samples taken at half-hour intervals, and the nitrogen selectivity could reach 5%.

[0214] Example 8

[0215] This embodiment adopts Figure 2 The device shown in the figure, the method for preparing the catalyst comprises the following steps:

[0216] The sedimentation tank 8 is filled with 150 mL of a mixed solution at a temperature of 25 to 32°C. The mixed solution includes 0.5 mol·L -1 NH4Cl, 0.5mmol·L -1 Cu(NO3)2 and 0.5mmol·L -1The solution tank 13 is filled with the same solution as that in the deposition tank 8. The electrochemical workstation 6 is turned on, and voltage is applied to the membrane electrode 7 and the counter electrode 9. The solution in the solution tank 13 flows from top to bottom through the conductive porous membrane driven by the pressure difference of the metering pump 12 to perform flow-pulse electrodeposition. The deposited solution enters the deposition tank 8; wherein the metal ions in the solution are uniformly deposited on the surface and pores of the conductive porous membrane to complete the deposition.

[0217] The conductive porous membrane is a tubular carbon membrane with an average pore size of 8.3 nm (electrode area of ​​28 cm 2 ), seal one end of the tubular carbon membrane with epoxy glue, which is the cathode, platinum sheet as the anode (counter electrode), saturated calomel electrode as the reference electrode, so that the metal salt solution in the solution tank flows from the top to the bottom through the hollow tube of the membrane tube in the tubular carbon membrane driven by the pressure difference, and flows out from the membrane pores, while applying a pulse electric field on the surface of the cathode electrode. Set the processing conditions: transmembrane pressure difference 80kPa, working voltage -0.8Vvs.SCE, pulse current density: 10~100mA / cm 2 In each pulse unit: the power-on time of a single pulse is 0.4s, the power-off time is 0.05s, and the number of pulses is 84; the interval between two pulse units is 280s, and the total deposition time is 134.4s. After the reaction is completed, the tubular carbon membrane with deposited metal is taken out, rinsed with deionized water several times, and then soaked in deionized water, changing the water every 6h for 48h, and dried at room temperature for use.

[0218] The preparation method is used to obtain a tubular carbon membrane catalyst loaded with Pd and Cu, wherein the percentage of Pd in ​​the total mass of the tubular carbon membrane is 0.003%, and the percentage of Cu in the total mass of the tubular carbon membrane is 0.003%.

[0219] Electrocatalytic reduction of nitrate nitrogen experiment

[0220] The electrocatalytic reduction of nitrate nitrogen experiment was carried out using the tubular carbon membrane loaded with Cu and Pd as the membrane electrode. The experimental processing steps were the same as the electrocatalytic reduction of nitrate nitrogen experimental steps in Example 1.

[0221] Conclusion: The carbon film catalyst loaded with Cu and Pd was used for the electrocatalytic reduction of nitrate nitrogen. During the 10-hour reaction, the single-pass removal rate of nitrate nitrogen reached 62% in the samples taken at half-hour intervals, and the nitrogen selectivity could reach 54%.

[0222] Although the above describes the specific implementation methods of the present invention, it does not limit the scope of protection of the present invention. Based on the technical solution of the present invention, various modifications or variations that can be made by those skilled in the art without creative work are still within the scope of protection of the present invention.

Claims

1. A method for preparing a catalyst, characterized in that: The steps include: Driven by pressure difference, a solution containing the metal to be deposited flows through the pores of the conductive porous carrier material to perform pulse electrodeposition to obtain a catalyst in which the metal is loaded on the conductive porous carrier material.

2. The method for preparing a catalyst according to claim 1, wherein: The conductive porous carrier material includes one or more of metal film, carbon film, carbide film, polymer film, composite film, carbon aerogel, nickel foam, carbon cloth and materials obtained by surface modification of the above materials; wherein the composite film is selected from metal / metal oxide composite film or metal / metal composite film; Preferably, the conductive porous carrier material is selected from tubular carbon membrane, tubular niobium carbide membrane, hollow fiber copper membrane or carbon cloth; More preferably, the conductive porous support material is selected from tubular carbon membrane, carbon cloth or tubular niobium carbide membrane.

3. The method for preparing a catalyst according to claim 1 or 2, wherein: The average pore size of the conductive porous carrier material is 1 nm to 2 μm; Preferably, the average pore size of the conductive porous carrier material is 1 nm to 1 μm; More preferably, the average pore size of the conductive porous support material is 1 to 200 nm.

4. The method for preparing a catalyst according to any one of claims 1 to 3, wherein: The solution containing the metal to be deposited contains one or more metal salts; Preferably, the solution contains a metal salt at a concentration of 0.1 to 10 mmol / L, calculated as metal atoms; Or, preferably, the solution contains two or more metal salts, and the concentration of each metal atom is 0.05 to 5 mmol / L, calculated as metal atoms.

5. The method for preparing a catalyst according to claim 4, wherein: The metal is a metal with catalytic activity; Preferably, the metal is selected from one or more of Pt, Pd, Rh, Ru, Ir, Au, Ag, Cu, Fe, Ni, Co, Cr, Zn and Ba; More preferably, the metal is selected from one or more of Pt, Pd, Ru, Ir, Au, Ag and Cu; Further preferably, the metal is a combination of Cu and Pd; further preferably, the mass ratio of Cu to Pd is 1-3:1-3; Or, further preferably, the metal is a combination of Pt and Ir; and even more preferably, the mass ratio of Pt to Ir is 1-3:1-3.

6. The method for preparing a catalyst according to any one of claims 1 to 5, wherein: The solvent used in the solution containing the metal to be deposited is water; Preferably, the temperature of the solution is 25-32°C.

7. The method for preparing a catalyst according to any one of claims 1 to 6, wherein: The pressure difference drive is to use a metering pump to control the pressure difference; And / or, preferably, a solution containing the metal to be deposited flows into the pores on one side of the conductive porous support material and flows out from the pores on the other side; And / or, preferably, the transmembrane pressure difference is 50-100 kPa; more preferably, the transmembrane pressure difference is 50-70 kPa.

8. The method for preparing a catalyst according to any one of claims 1 to 7, wherein: The conditions of the pulse electrodeposition are: the working voltage of the external power supply is -1.2 to -0.2 V vs SCE; and / or, pulse current density 10 to 100 mA cm -2 .

9. The method for preparing a catalyst according to claim 8, wherein: The single pulse power-on time in each pulse unit is 0.01 to 1 s; preferably, the single pulse power-on time in each pulse unit is 0.1 to 0.7 s; more preferably, the single pulse power-on time in each pulse unit is 0.2 to 0.6 s; further preferably, the single pulse power-on time in each pulse unit is 0.3 to 0.5 s; And / or, the time of a single power-off in each pulse unit is 0.005 to 20 seconds; preferably, the time of a single power-off in each pulse unit is 0.005 to 10 seconds; more preferably, the time of a single power-off in each pulse unit is 0.005 to 1 second; further preferably, the time of a single power-off in each pulse unit is 0.005 to 0.5 seconds; And / or, the number of pulses of each pulse unit is 40 to 200 times; preferably, the number of pulses of each pulse unit is 40 to 150 times; more preferably, the number of pulses of each pulse unit is 40 to 100 times; further preferably, the number of pulses of each pulse unit is 70 to 100 times.

10. The method for preparing a catalyst according to claim 8 or 9, wherein: The interval time between two pulse units is 0.1 to 500 s; preferably, the interval time between two pulse units is 100 to 500 s; more preferably, the interval time between two pulse units is 150 to 500 s; further preferably, the interval time between two pulse units is 300 to 500 s; And / or, the total deposition time is 0.8 to 800 s; preferably, the total deposition time is 0.8 to 500 s; more preferably, the total deposition time is 0.8 to 200 s; further preferably, the total deposition time is 50 to 150 s.

11. A catalyst, characterized in that It is prepared by the preparation method described in any one of claims 1 to 10.

12. The catalyst according to claim 11, wherein The particle size of the metal deposited in the catalyst is the diameter of the metal atom; And / or, the percentage of the metal deposited in the catalyst to the total mass of the conductive porous carrier material is: greater than 0 and less than or equal to 0.1%; preferably, the percentage of the metal deposited in the catalyst to the total mass of the conductive porous carrier material is: greater than 0 and less than or equal to 0.05%; more preferably, the percentage of the metal deposited in the catalyst to the total mass of the conductive porous carrier material is: greater than 0 and less than or equal to 0.02%; further preferably, the percentage of the metal deposited in the catalyst to the total mass of the conductive porous carrier material is: greater than 0 and less than or equal to 0.015%.

13. Use of the catalyst according to claim 11 or 12 in the field of electrocatalytic degradation of pollutants or electrocatalytic reduction of carbon dioxide; Preferably, the catalyst is used in the field of electrocatalytic reduction treatment of nitrate nitrogen; Or, preferably, the catalyst is used in the field of electrocatalytic oxidation treatment of benzyl alcohol; Or, preferably, the catalyst is used in the field of electrocatalytic oxidation treatment of phenol.

Citation Information

Patent Citations

  • Method for preparing porous carbon membrane

    CN102107123A